PENERAPAN PRINSIP GOOD GOVERNANCE DALAM HUKUM ADMINISTRASI NEGARA: ANALISIS YURIDIS ATAS AKUNTABILITAS, TRANSPARANSI, DAN PARTISIPASI PUBLIK - Samsul Arifin; Mohammad Rifa'i (INTELIGENSIA MEDIA, 2026)
The application of good governance principles is a fundamental element in the implementation of democratic and law-based governance. In the context of state administrative law, the principles of accountability, transparency, and public participation serve as instruments for controlling administrative authority and protecting citizens' rights. This study aims to analyse the application of these good governance principles within the framework of state administrative law in Indonesia through a juridical approach. The research method used is qualitative research in the form of library research, which examines primary, secondary, and tertiary legal materials, including legislation, legal doctrines, and Scopus-indexed scientific journal articles. Data analysis is carried out in a legal-normative manner using a conceptual and legislative approach. The results of the study show that although the principles of accountability, transparency, and public participation have a strong normative basis, their implementation in the practice of governance still faces various obstacles. Accountability tends to be formal, transparency is not yet fully substantive, and public participation is still limited to procedural fulfilment. This study concludes that strengthening the application of good governance principles in state administrative law requires consistency in implementation, increased capacity of the apparatus, and effective oversight mechanisms to realise a democratic, just, and public interest-oriented government